Effects of stimulus disparity on acquisition of sight word sets: Manipulation of initial letter. Issue 1 (5th October 2022) - Chotto, Jensen; Lozy, Erica D.; Marin, Rachel; Donaldson, Jeanne M.
Abstract : Due to the prevalence of words that cannot be read phonetically in the English language, sight word instruction is required to supplement phonics instruction. In this study, we manipulated stimulus disparity in sight word sets by comparing the effects of sets of sight words with the same initial letter (3 words per set, 3 total sets) versus distributing words with the same initial letter across sets when assessing acquisition of the combined set (9 words) for 5 children who ranged from 4–6 years of age using a combined adapted alternating treatments design and pre‐posttest design. All participants mastered the 3‐word sets in both teaching conditions but did not master the control sets. In general, participants required more teaching sessions when the words in sets began with the same letter. These findings are consistent with stimulus disparity research demonstrating that discrimination training is generally less efficient when comparison stimuli are similar.